The Effect of Exercises and Medicine Apparatuses on the Treatment of Lumber Disc Herniation in women aged 25 – 30 years Old - Abedulrazaaq, Badaa (Journal of Physical Education, 2016)
Lumber discs are important in performing daily activities and injuries in this disc can be very devastating to individuals in some cases lead to paralysis. The researcher designed a nutritional program along with rehabilitation exercises to decrease the risks on this injury and as a precaution against surgery. The aim of the research was designing rehabilitation exercises with medicine apparatuses to treat women with lumber disc herniation aged 25 – 30 years old. The researcher performed the program in a medical rehabilitation and joint diseases center. The subjects were tested in weight, spine flexibility and many other tests. The results showed slight development in posttests due to the slight pain felt by the patient. The researcher concluded that rehabilitation exercises have a great role in treatment and works against muscle atrophy. In addition to that progression in exercises gave patients motivation and the nutritional program played a great role in decreasing back pain due to patients weight loses. Finally the researcher recommended using illustration of exercises to perform exercises correctly and she also recommended using this program on other subjects for other injuries like knee injuries